Double sum to infinity

Calculus Level 4

k = 1 ( 1 ) k 1 k n = 0 300 2 n k + 5 = ? \large \sum_{k=1}^{\infty} \dfrac{(-1)^{k-1}}{k} \sum_{n=0}^{\infty} \dfrac{300}{2^n k+5}=?

the sum does not converge 24 137 567

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Sangchul Lee
Mar 28, 2019

We consider a more general setting. Let z > 0 z > 0 . Then k = 1 ( 1 ) k 1 k n = 0 1 2 n k + z = k = 1 ( 1 ) k 1 k n = 0 0 1 x 2 n k + z 1 d x = 0 1 ( n = 0 k = 1 ( 1 ) k 1 k x 2 n k ) x z 1 d x = 0 1 ( n = 0 log ( 1 + x 2 n ) ) x z 1 d x , \begin{aligned} \sum_{k=1}^{\infty}\frac{(-1)^{k-1}}{k} \sum_{n=0}^{\infty}\frac{1}{2^n k+ z} &= \sum_{k=1}^{\infty}\frac{(-1)^{k-1}}{k} \sum_{n=0}^{\infty} \int_{0}^{1} x^{2^n k + z - 1} \, \mathrm{d}x \\ &= \int_{0}^{1} \left( \sum_{n=0}^{\infty} \sum_{k=1}^{\infty}\frac{(-1)^{k-1}}{k} x^{2^n k} \right) x^{z - 1} \, \mathrm{d}x \\ &= \int_{0}^{1} \left( \sum_{n=0}^{\infty} \log(1 + x^{2^n}) \right) x^{z - 1} \, \mathrm{d}x, \end{aligned} where in the last step we utilized the Taylor expansion log ( 1 + x ) = k = 1 ( 1 ) k 1 k x k \log(1+x) = \sum_{k=1}^{\infty} \frac{(-1)^{k-1}}{k} x^k . Now, from the following famous (and easy-to-prove) identity 1 1 x = n = 0 ( 1 + x 2 n ) , \frac{1}{1-x} = \prod_{n=0}^{\infty} (1 + x^{2^n}), the last step simplifies to = 0 1 x z 1 log ( 1 1 x ) d x = [ x z 1 z log ( 1 1 x ) ] 0 1 + 1 z 0 1 1 x z 1 x d x = H ( z ) z , \begin{aligned} &= \int_{0}^{1} x^{z - 1} \log\left(\frac{1}{1-x}\right) \, \mathrm{d}x \\ &= \left[ \frac{x^z - 1}{z} \log\left(\frac{1}{1-x}\right) \right]_{0}^{1} + \frac{1}{z} \int_{0}^{1} \frac{1 - x^z}{1 - x} \, \mathrm{d}x \\ &= \frac{H(z)}{z}, \end{aligned} where H ( z ) H(z) is the harmonic number. Plugging z = 5 z = 5 , we end up with k = 1 ( 1 ) k 1 k n = 0 1 2 n k + 5 = H ( 5 ) 5 = 1 5 ( 1 + 1 2 + 1 3 + 1 4 + 1 5 ) = 137 300 , \sum_{k=1}^{\infty}\frac{(-1)^{k-1}}{k} \sum_{n=0}^{\infty}\frac{1}{2^n k+ 5} = \frac{H(5)}{5} = \frac{1}{5}\left(1 + \frac{1}{2} + \frac{1}{3} + \frac{1}{4} + \frac{1}{5} \right) = \frac{137}{300}, and multiplying 300 to both sides yields the answer 137 137 .

How did you get the second step in the final integration? From where the 1's appear in the integration by parts technique?

A Former Brilliant Member - 2 years, 2 months ago

Log in to reply

Are you asking how the integration by parts is done in the last step? I am simply using the fact that x z 1 z \frac{x^z - 1}{z} is an antiderivative of x z 1 x^{z-1} . This particular choice of antiderivative is essential for this improper integral, for otherwise the logarithmic singularity of log ( 1 1 x ) \log\left(\frac{1}{1-x}\right) at x = 1 x = 1 cannot be cancelled out.

Sangchul Lee - 2 years, 2 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...